Estudo comparativo entre alguns benzalpiruvatos-fenil substituído de lantanídeos e ítrio no estado sólido. - Fernandes, N. S.; Carvalho, MAD; Leles, MIG; Ionashiro, Massao [UNESP] (Editora Unesp, 1999)
In the present work, the thermal decomposition step of some lanthanides and yttrium compounds involving different ligand phenyl-substituted derivatives of benzylidenepyruvate was appraised by thermogravimetry (TG). A correlation about the metal ions content was made by comparison of the results obtained by TG and EDTA complexometry.
Comparative study between some lanthanides and yttrium compounds involving different ligand phenyl-substituted derivatives of benzylidenepyruvate in the solid state.
Keywords: thermogravimetry (TG); benzylidenepyruvate; lanthanides; yttrium